Mechanism Study of the Protective Effects of Sodium Tanshinone IIA Sulfonate Against Atorvastatin-Induced Cerebral Hemorrhage in Zebrafish: Transcriptome Analysis - Zhou, Zhong-Yan; Zhao, Wai-Rong; Xiao, Ying; Zhang, Jing; Tang, Jing-Yi; Lee, Simon Ming-Yuen (Frontiers in Pharmacology, 2020)
Hemorrhage stroke is a severe vascular disease of the brain with a high mortality rate in humans. Salvia miltiorrhiza Bunge (Danshen) is a well-known Chinese Materia Medica for treating cerebral vascular and cardiovascular diseases in traditional Chinese medicine. Sodium tanshinone IIA sulfonate (STS) is a water-soluble derivative of tanshinone IIA, which is the main active ingredient of Danshen. In our previous study, we established a zebrafish model of cerebral hemorrhage and found that STS dramatically decreased both the hemorrhage rate and hemorrhage area, although the underlying mechanism was not fully elucidated. We conducted transcriptome analysis of the protective effect of STS against atorvastatin (Ator)-induced cerebral hemorrhage in zebrafish using RNA-Seq technology. RNA-Seq revealed 207 DEGs between the Ator-treated group and control group; the expression levels of 53 DEGs between the Ator-treated group and control group were reversed between the STS+Ator-treated group and Ator-treated group. GO enrichment analysis indicated that these 53 DEGs encode proteins with roles in hemoglobin complexes, oxygen carrier activity and oxygen binding, etc. KEGG analysis suggested that these 53 DEGs were most enriched in three items, namely porphyrin and chlorophyll metabolism, ferroptosis and the HIF-1 signaling pathway. The PPI network analysis identified 12 hub genes, and we further verified that Ator elevated the mRNA expression levels of hemoglobin (hbae1.3, hbae3, hbae5 hbbe2 and hbbe3), carbonic anhydrase (cahz), HIF-1 (hif1al2) and Na+/H+ exchanger (slc4a1a and slc9a1) genes, while STS significantly suppressed these genes. In addition, we found that pharmacological inhibition of PI3K/Akt, MAPKs and mTOR signaling pathways by PI3K, Akt and MAPK inhibitors partially attenuated the protective effect of STS against Ator-induced cerebral hemorrhage in zebrafish, regardless of mTOR inhibition. We concluded that hemoglobin, carbonic anhydrase, Na+/H+ exchanger and HIF-1 genes might be potential biomarkers of Ator-induced cerebral hemorrhage in zebrafish, as well as pharmacological targets of STS. Moreover, HIF-1 and its regulators, i.e., the PI3K/Akt and MAPK signaling pathways, were involved in the protective effect of STS against Ator-induced cerebral hemorrhage. This study also provided evidence of bio-markers involved in hemorrhage stroke and improved understanding of the effects of HMG-COA inhibition on vascular permeability and cerebral hemorrhage.